Tradisi Hidangan Olahan Asal Bulus (Trionyx cartilaginous) dan Analisis Nilai Gizinya (TRADITION AND SOCIAL CULTURES OF MEAL AND NUTRITIVE VALUES OF FOODSTUFFS ORIGINATED FROM FRESH WATER TURTLE (Trionyx cartilagineus)) - Arka, Ida Bagus (Jurnal Veteriner, 2016)
Tradisi Hidangan Olahan Asal Bulus ( Trionyx cartilaginous ) dan Analisis Nilai Gizinya   (TRADITION AND SOCIAL CULTURES OF MEAL AND NUTRITIVE VALUES OF FOODSTUFFS ORIGINATED FROM FRESH WATER TURTLE (Trionyx cartilagineus))
Keywords: Traditions and social cultures; meal preparations; fresh water turtle; nutritive values